Marketing strategy of Premier Communications & Engineering Sdn Bhd. as a sole distributor of Northern Telecom's Meridian SL-1 PABX system in Malaysia / Mohd Nazri Mohd Lotfi - Mohd Lotfi, Mohd Nazri (1991)
Premier Communication & Engineering Sdn Bhd is a sole distributor of the Meridian SL-1 PABX system in Malaysia. The Meridian SL-1 is a renown digital PABX system in the world, developed by Northern Telecom of Canada.